Malcolm Forbes : the man who had everything - Winans, Christopher (New York : St. Martin's Press, 1990)
This is a story of both men: the fiercely independent, flamboyantly social entrepreneur who created a dynasty-and the secretly lonely closeted person who suffered a longing no amount of fame or fortune could ever mitigate.
"A Thomas Dunne book."
Includes index.
Keywords: Forbes, Malcolm S; Forbes; Businesspeople -- United States -- Biography; Capitalists and financiers -- United States -- Biography